2021
DOI: 10.1155/2021/5512755
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Orofacial Pain and Dental Health Status and Oral Health Behaviours in Facial Burn Patients

Abstract: This study aims to examine the association of orofacial pain and oral health status and oral health behaviours in facial burn patients. The participants in this cross-sectional study were randomly recruited from the Burn Care Center, Institute of Medical Sciences, Islamabad, Pakistan. An intraoral evaluation was carried out to record the DMFT and OHI-S. A self-administered questionnaire was used to collect information on sociodemographic status, brushing frequency, and dental visits. Orofacial pain during mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…These observations are similar to the studies by Farsi N et al, Chaffee BW et al, and Almusawi et al, where similar risk factors were prevalent [9,13,16]. Previous studies have established the risk of caries and their relationship with plaque, deep pits and fissures, and frequency of food intake [17,18]. When associated with an enamel defect, plaque may exponentially increase caries risk [19,20].…”
Section: Discussionsupporting
confidence: 86%
“…These observations are similar to the studies by Farsi N et al, Chaffee BW et al, and Almusawi et al, where similar risk factors were prevalent [9,13,16]. Previous studies have established the risk of caries and their relationship with plaque, deep pits and fissures, and frequency of food intake [17,18]. When associated with an enamel defect, plaque may exponentially increase caries risk [19,20].…”
Section: Discussionsupporting
confidence: 86%
“…These consequences result in economic loss either in terms of financial loss, rehabilitation, or decreased productivity [ 3 , 4 , 7 ]. The unilateral excessive stresses on muscles, joints, and nerves for a long period, together with elevated unsupported arms, the vibration of instruments, and maintaining an awkward static position for a long time during the dental procedures result in WMSDs [ 3 , 8 , 9 ]. The lower back, shoulder, hands, and arms are some of the most frequently reported body areas affected with MSD among dentists.…”
Section: Introductionmentioning
confidence: 99%
“…36 Overall, the dental community was found to be endangered to practice in the current situation, which might be an influence of vast media coverage, lack of technical equipment and shortage of personal protective equipment (PPE), extended working hours, and many other reasons. 37,38 Moreover, in this study, it was concluded that dental staff exhibited greater psychological stress problems amid this pandemic because of greater exposure to risk. This finding is relevant to the study that showed unwillingness by dentists to treat patients diagnosed with some infectious diseases like HIV 39,40 and tuberculosis.…”
Section: Discussionmentioning
confidence: 64%